2022
DOI: 10.1039/d2ra03503k
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode (LED)-directed green synthesis of silver nanoparticles and evaluation of their multifaceted clinical and biological activities

Abstract: LEDs-mediated green synthesis of silver nanoparticles, their characterization and biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Recently, Anjum et al , and Shah et al , reported harmonizing results indicating that ZnONPs had the potential to be utilized as anti-aging agents. 39,41 The statistical analysis showed that IV-ZnONPs had significantly greater anti-aging potential as compared to CS-ZnONPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Anjum et al , and Shah et al , reported harmonizing results indicating that ZnONPs had the potential to be utilized as anti-aging agents. 39,41 The statistical analysis showed that IV-ZnONPs had significantly greater anti-aging potential as compared to CS-ZnONPs.…”
Section: Resultsmentioning
confidence: 99%
“…The CUPRAC assay was carried out in accordance with Anjum et al , protocol. 41 1 mL of 99.99% copper chloride, 1 mL of 1 M acetate buffer (pH 7), and 1 mL of neocuproine solution were mixed. After adding 1 mL of distilled water to 1 mL of ZnONPs, the mixture was allowed to incubate for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface properties of silver nanoparticles obtained with citrate or the sphagnum extract were evaluated using FT-IR spectroscopy. This technique is often used to identify the functional groups that are present in active plant ingredients [ 32 ]. In the IR spectrum of the sphagnum extract ( Figure 1 A), the wide and intense peak in the region of 3500–2500 cm −1 indicates the presence of hydroxyl groups, and the very intense band at 1051 cm −1 most likely belongs to C-O stretching vibrations in alcohol or ether bonds.…”
Section: Resultsmentioning
confidence: 99%
“…These cells are well-studied and have a high rate of cell division, making them ideal for this type of research [ 50 , 51 ]. Moreover, AgNPs are widely used in consumer aerosol products due to their antibacterial ability; so, there is a risk of their ingestion and deposition in the respiratory tract [ 32 ]. Initially, standard colorimetric assays, the MTT test and the rezazurin reduction method, were used to assess the cytotoxic effect of silver nanoparticles on mammalian cells.…”
Section: Resultsmentioning
confidence: 99%